2015
DOI: 10.1038/icb.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

The MS4A family: counting past 1, 2 and 3

Abstract: The MS4A (membrane-spanning 4-domain family, subfamily A) family of proteins contains some well-known members including MS4A1 (CD20), MS4A2 (FcɛRIβ) and MS4A3 (HTm4). These three MS4A family members are expressed on the cell surface of specific leukocyte subsets and have been well characterized as having key roles in regulating cell activation, growth and development. However, beyond MS4A1-3 there are a large number of related molecules (18 to date in humans) where our understanding of their biological roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 100 publications
(258 reference statements)
4
78
0
Order By: Relevance
“…To screen for potential non-GPCR odorant receptors, the RNAseq data were filtered to identify transmembrane protein families that exhibit sufficient molecular diversity to potentially interact with a wide range of ligands. As detailed below, this screen identified the Membrane Spanning, 4-pass A ( Ms4a ) genes, which encode a class of four-transmembrane (4TM) spanning proteins that are structurally distinct from GPCRs (Eon Kuek et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To screen for potential non-GPCR odorant receptors, the RNAseq data were filtered to identify transmembrane protein families that exhibit sufficient molecular diversity to potentially interact with a wide range of ligands. As detailed below, this screen identified the Membrane Spanning, 4-pass A ( Ms4a ) genes, which encode a class of four-transmembrane (4TM) spanning proteins that are structurally distinct from GPCRs (Eon Kuek et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Previous biochemical studies relied upon clustering antibodies to trigger MS4A1-mediated calcium flux (Janas et al, 2005); this and related work suggested that the MS4As may facilitate increases in intracellular calcium by acting as co-receptors for associated ligand-binding proteins such as the B-cell receptors (Dombrowicz et al, 1998; Eon Kuek et al, 2015). However, interpreting these experiments has been difficult in light of possible gains-of-function imposed by the use of clustering reagents; here we show that small molecule ligands cause an MS4A-dependent influx of extracellular calcium, demonstrating that the MS4A molecules themselves have a receptor function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane-spanning 4-domain subfamily A ( MS4A ) gene cluster is present on chromosome 11q12 and includes eighteen genes spanning approximately 600kb [45–47]. Multiple GWAS in European and Asian populations have implicated several genes within the MS4A cluster in AD, including MS4A4A , MS4A4E , MS4A6A , and MS4A6E [23, 4851].…”
Section: Ad Gwas Studiesmentioning
confidence: 99%
“…Members of this family were previously studied in the context of calcium signaling in the immune system, although their ligands were unknown (Eon Kuek et al, 2016). Both in vivo and in vitro analyses clearly demonstrate that the MS4As fulfill the expected criteria of odorant receptors.…”
mentioning
confidence: 92%